A single NLR gene confers resistance to leaf and stripe rust in wheat - Sharma, Davinder; Avni, Raz; Gutierrez-Gonzalez, Juan; Kumar, Rakesh; Sela, Hanan; Prusty, Manas Ranjan; Shatil-Cohen, Arava; Molnár, István; Holušová, Kateřina; Said, Mahmoud; Doležel, Jaroslav; Millet, Eitan; et al. (Nature communications, 2024)
Nucleotide-binding leucine-rich repeat (NLR) disease resistance genes typically confer resistance against races of a single pathogen. Here, we report that Yr87/Lr85, an NLR gene from Aegilops sharonensis and Aegilops longissima, confers resistance against both P. striiformis tritici (Pst) and Puccinia triticina (Pt) that cause stripe and leaf rust, respectively. Yr87/Lr85 confers resistance against Pst and Pt in wheat introgression as well as transgenic lines. Comparative analysis of Yr87/Lr85 and the cloned Triticeae NLR disease resistance genes shows that Yr87/Lr85 contains two distinct LRR domains and that the gene is only found in Ae. sharonensis and Ae. longissima. Allele mining and phylogenetic analysis indicate multiple events of Yr87/Lr85 gene flow between the two species and presence/absence variation explaining the majority of resistance to wheat leaf rust in both species. The confinement of Yr87/Lr85 to Ae. sharonensis and Ae. longissima and the resistance in wheat against Pst and Pt highlight the potential of these species as valuable sources of disease resistance genes for wheat improvement.
Keywords: alely; Genes, Plant; Disease Resistance; Alleles; odolnost vůči nemocem; Plants, Genetically Modified; rostlinné geny; Plant Leaves; Basidiomycota; pšenice; NLR proteiny; rostlinné proteiny; geneticky modifikované rostliny; fylogeneze; Plant Proteins; nemoci rostlin; Puccinia; Aegilops; Triticum; Phylogeny; listy rostlin; NLR Proteins; Plant Diseases